2022
DOI: 10.1111/1462-2920.16035
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the onset of B12‐based mutualisms using a recently evolved Chlamydomonas auxotroph and B12‐producing bacteria

Abstract: Summary Cobalamin (vitamin B12) is a cofactor for essential metabolic reactions in multiple eukaryotic taxa, including major primary producers such as algae, and yet only prokaryotes can produce it. Many bacteria can colonize the algal phycosphere, forming stable communities that gain preferential access to photosynthate and in return provide compounds such as B12. Extended coexistence can then drive gene loss, leading to greater algal–bacterial interdependence. In this study, we investigate how a recently evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 86 publications
3
15
0
Order By: Relevance
“…1C, p > 0.05). Although the maximum density of M. japonicum in coculture without sucrose (∼3x10 7 –5x10 8 CFU/ml) was similar to what has been observed previously [27], we found that the bacterium was able to achieve a comparable density without the alga.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…1C, p > 0.05). Although the maximum density of M. japonicum in coculture without sucrose (∼3x10 7 –5x10 8 CFU/ml) was similar to what has been observed previously [27], we found that the bacterium was able to achieve a comparable density without the alga.…”
Section: Resultssupporting
confidence: 89%
“…5D). This demonstrated that greater algal density does not translate into greater M. japonicum growth, as noted previously [27].…”
Section: Reductively Dividing Bacteria Still Deliver Sufficient Vitam...supporting
confidence: 72%
“…Purine externalization is not dependent on E. coli or growth conditions. In some cross-feeding systems, the recipient can influence metabolite externalization by a producer (30)(31)(32). To test whether E. coli induces R. palustris purine externalization, we inoculated E. coli ΔpurH into media supplemented with R. palustris monoculture supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic signatures could be more diverse than the repertoire of cross-fed metabolites. Metabolite externalization can also be conditional (2, 31, 32, 41) and need not even require a genetic signature in the producer. Previously we found that enhanced metabolite acquisition by a recipient was sufficient to stimulate more NH 4 + release by a producer and establish cross-feeding; the genetic signature was in the recipient (30).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, mass spectrometry revealed very low levels of cobalamin (a benzimidazolyl cobamide) in the same cell extracts, supporting this prediction. A wealth of studies exist that predict the existence of cobamide sharing between microorganisms (9,(11)(12)(13)(14)(15)(16)(17)42), and of these, a number provide direct experimental evidence for this phenomenon, although they are almost exclusively restricted to those between bacteria and cobamide-requiring eukaryotes (43)(44)(45)(46). Evidence of cobamide sharing between two or more bacterial species is limited, potentially due to a lack of experimental models to measure this phenomenon and the non-auxotrophic nature of many cobamide-utilizing bacteria (9).…”
Section: Discussionmentioning
confidence: 99%